Guided Inquiry-Based Worksheet Development to Improve Critical Thinking Skills on Colloidal Properties Sub Material - Anggraeni Puspita Sari; Harun Nasrudin (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: Guided Inquiry-Based Worksheet Development to Improve Critical Thinking Skills on Colloidal Properties Sub Material. According to the background of the problem obtained in the pre-research. So this study was conducted to determine the feasibility of a guided inquiry-based worksheet to improve critical thinking skills on colloidal properties sub material. There are three aspects to determine the feasibility of the developed worksheet, namely validity, practicality, and effectiveness. This research uses a Research Development (RD). The limited trial was tested on 15 class XII MIPA 6 at State High School 3 Sidoarjo. The research result shows that the developed worksheet is valid in content validity, a percentage of 90%, and construct validity of 84%. Moreover, all of them got a very valid category. Practicality gets an average student response of 79%, and participant observation students by 79% overall got the practical category. Effectiveness is obtained based on pretest and posttest results of critical thinking skills, with an n-gain score in the range of 0.521-0.938 in the medium to high criteria.Keywords: Worksheet feasibility, guided inquiry, critical thinking skills, colloidal properties. DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.03